Features of transport of potassium ions in ischemia-reperfusion syndrome of lower extremities, abdominal trauma and hypovolemic shock - Tsymbaliuk, G. Y.; Krylyuk, V. O. (Journal of Education, Health and Sport, 2018)
80 pubescent white male Wistar rats weighing 190-220 g were used in the experiment. Rats have been on a standard vivarium diet.Animals were divided into 1 control (CG) and 3 experimental groups (EG) (8 animals per group). Haemostatic tourniquets were applied for 120 minutes proximal to the lower paws of animals of the first experimental group under the thiopental-sodium anesthesia (40 mg kg-1). Applying of tourniquets caused the development of ischemic-reperfusion syndrome. Blunt abdominal trauma was simulated in the second experimental group by applying two strikes to the abdomen; Hypovolemic shock was modeled in a group by cutting the femoral vessels and bloodletting from 20 to 22% of the circulating blood volume. Injuries of the third experimental group were combination of injuries of the first two groups. Animals of the control group were inducted into the anesthesia without any injury. The functional status of the kidneys of experimental animals was determined by the method of water loading at 1st, 3rd and 7th day. The concentration of potassium ions was determined in urine and blood serum and the level of its proximal and distal transport, as well as excretion, were calculated. Animals of experimental groups were withdrawn from the experiment by the method of total blood-flow from the heart under thiopental sodium anesthesia.Thus, simulated injuries are accompanied by a significant increasing potassium level in serum in all experimental groups. Moreover, in EG-1 there was a tendency of gradual decrease of indicator on 7 day of observation, in contrast to the indicators in EG-2 and EG-3 where increased on 7 day. In all EG the maximum increase of the indicator was observed on the 1 day of the post-traumatic period. The simulation of various causes of mechanical trauma leads to a significant increase of the excretion of potassium ions in the urine, with the exception of injuries of the abdominal trauma with massive blood loss and applied haemostatic tourniquets on both lower limbs, when on the 7 day the indicator is approaching the level of control group. This can be explained by a significant decrease of diuresis in the experimental group.